Determinant of Depression in Multi - Drug Resistant Tuberculosis (MDR) at Waled Cirebon Regional General Hospital - Endah Sari Purbaningsih; Muadi Muadi; Thia Oktiany; Rosalia Rahayu; Lili Wahyuni; Ani Nurhaeni; Dewi Erna Marisa (Poltekkes Kemenkes Palu, 2025)
Depression is a common psychological complication among patients with multidrug-resistant tuberculosis (MDR-TB), affecting treatment adherence and recovery outcomes. Identifying the determinants of depression in this population is essential for developing comprehensive care strategies. This cross-sectional study was conducted among 28 MDR-TB patients at RSUD Waled. Data on demographic, clinical, and psychosocial variables were collected through structured questionnaires. Depression was assessed using a standardized screening tool. Bivariate analysis was performed using chi-square tests, followed by multivariate logistic regression to identify independent predictors of depression. The bivariate analysis showed no significant association between age (p=0.063), gender (p=0.07), income (p=0.065), or educational attainment (p=0.63) with depression, indicating that these demographic and socioeconomic factors did not influence depressive outcomes. In contrast, comorbidities (p<0.001), duration of illness (p=0.011), and community stigma (p<0.001) were significantly associated with depression. Respondents with comorbidities, longer illness duration, and negative community stigma were markedly more likely to experience depression, suggesting that clinical and psychosocial factors are stronger determinants than demographic variables. Comorbidities, longer illness duration, and community stigma were significantly related to depressive outcomes. Future research with larger and more diverse populations is needed to validate these findings and explore contextual factors influencing depression in MDR-TB patients.